History-like Path of Identical Particle Systems in Topological SpaceM - Bama, Akhmad Aminuddin (Jurnal Fisika dan Aplikasinya, 2010)
In this paper, a new concept has been introduced related to the construction of inequivalent quantizations for a system, which is called â€œhistory-like pathâ€ for particles. This is a collection of non-causal homotopical paths. Each homotopy class of paths will be labelled with a â€œwordâ€ constructed from the generators of fundamental group 1(QN(i)) of a configuration space of the system in a space-like i which is a deformation retract of Mi region that is a sub-space-time of M in which there is no singular slice (a slice Mc in M that contains a singular point). The labels determine the generators and their relations in constructing the fundamental group 1(QN) of the system.